2006
DOI: 10.1136/jcp.2005.028357
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of molecular markers for improved detection of breast cancer metastases in sentinel nodes

Abstract: Background and objectives:In patients with breast cancer (BC), the sentinel node (SN) is the first node in the axillary basin that receives the primary lymphatic flow and can be used to accurately assess the axillary nodal status without removal of the axillary contents. Currently, histology and/or immunohistochemistry are the routine methods of SN analysis. The primary objective of this study was to develop a reproducible reverse transcription (RT) PCR assay, with emphasis on achieving high specificity for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 69 publications
0
20
0
1
Order By: Relevance
“…Genetic markers such as TP53, VEGF, MAM, PTGS2, NME1, and other cancer genes (Abdul-Rasool et al, 2006;Nissan et al, 2006;Zhu et al, 2006) have been shown to have significant prognostic potential in breast cancer with respect to the axillary and systemic metastasis. New information is now emerging from the data obtained from genome-wide studies using high-throughput methodologies where many genes show different characteristics in expression profiles, which can affect the clinical outcome including the development of lymph node metastases (Bertucci et al, 2000;Ahr et al, 2001;van 't Veer et al, 2002).…”
mentioning
confidence: 99%
“…Genetic markers such as TP53, VEGF, MAM, PTGS2, NME1, and other cancer genes (Abdul-Rasool et al, 2006;Nissan et al, 2006;Zhu et al, 2006) have been shown to have significant prognostic potential in breast cancer with respect to the axillary and systemic metastasis. New information is now emerging from the data obtained from genome-wide studies using high-throughput methodologies where many genes show different characteristics in expression profiles, which can affect the clinical outcome including the development of lymph node metastases (Bertucci et al, 2000;Ahr et al, 2001;van 't Veer et al, 2002).…”
mentioning
confidence: 99%
“…Various studies have suggested that the combination of pathological evaluation and molecular analysis of SLNs yields the highest sensitivity for prediction of the pathological status of ALNs [18] as compared with IHC analysis [28], which in turn shows a higher metastasis detection rate than HE staining alone [11,29]. Expression of transcripts of several genes, including CK19, CEA, MGB1 and MGB2 and NY-BR-1, in SLN have been shown to increase the number of detected positive lymph nodes [28,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…[33][34][35][36] Additionally, multiple molecular markers, including hMAM-A and MAGE-A3, have been successfully used for detection of micrometastasis in breast sentinel lymph nodes. 37 However, the impact of these findings on clinical outcome is debatable, and it has been suggested that the clinical benefit of such additional evaluation, 18 including immunohistochemistry, in some cases may be limited. 23,24 Similar to these other organs, immunohistochemical evaluation of lymph nodes for occult metastases may be of value in directing prognosis and therapy for germ cell tumor patients who undergo retroperitoneal lymph node dissection, particularly if cases are categorized according to clinical suspicion.…”
Section: Discussionmentioning
confidence: 99%